PEMAHAMAN JIHAD KA LANG AN SI SWA TERN ATE Puritanisme tanpa Kekerasan - Kadir Ahmad (Al-Qalam, 2008)
This research aims to describe student of high school perspective onJihad. This research was conducted at three high schools in Ternate andtwo high schools in Makassar. Data was collected using questioner toamong 212 students of five high schools, and analyzed using quantitativemethod.The result of study indicates that (1) students of high school understoodJihad as struggling, sacrifice, war, and death as martyr; (2) this perspectiveof Jihad was influenced by social construction; (3) Although theirperspective tend to purity, but they reject the radicalism of religion assolution.